STORYTELLING DENGAN MEDIA BONEKA JARI: SUATU KEGIATAN SERVICE LEARNING DI MIS TUNAS ISLAM KABUPATEN BOGOR - Hasanah, Tita; Humairoh, Aninda Nishfi; Iswandi, Delia; Puspita, Mutiara; Fitriyani, Sagita; Maesaroh, Siti Patimah; A’yuni, Siti Qurrota; Hasanah, Siti Zulfah (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2024)
This Community Service Activity (PKM) aims to implement one of the media created by students from Seni Budaya Keterampilan (the Art and Culture Skills) course, namely finger puppets through storytelling activities. The method used is service learning. The activities were carried out at MIS Tunas Islam, Pamijahan District, Bogor Regency. The target of this service activity is first grade students. The activity stages consist of planning, implementation and evaluation. In general, this PKM activities ran well and smoothly and provided several recommendations for further activities.